Types and Abundance of Periphyton on Ceramics Substrate Placed in the Parit Belanda River, Rumbai Pesisir District, Pekanbaru City, Riau - Eka Dwinata Nopitasari; Asmika Harnalin Simarmata; Clemens Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Periphyton is a sessile microscopic organisms that are able to attach in some natural subsrates such as rocks, woods, plants and aquatic animals. Research aims to determine the type and abundance of periphyton attached in ceramic substrats in the Parit Belanda River has been carried out in March-April 2016. There were 2 types of ceramics used, the rough surfaced ceramics and smooth surfaced ceramics. There were three stations namely station 1 (in the up stream), station 2 (in the middle of the stream), and station 3 (in the down stream). Samplings were conducted once/week for a 4 weeks period. The periphyton samples were brushed from the ceramic surface (8 cm x 3 cm). Type of periphyton were identified based on Bigg and Killroy (2000), Yunfang (1995), and Presscot (1974). Result shown that there were 63 types of phytoperiphyton present, they were belonged to 5 classes, namely Bacillariophyceae (13 species), Chlorophyceae (10 species), Chrysophyceae (2 species), Cyanophyceae (7 species) Dinophyceae (2 spesies) and zooperiphyton are belonged to 7 classes, namely Cilliate (2 species), Euglenophyta (5 species), Monogononta (11 spesies), Oligotrichia (2 spesies), Protozoa (2 spesies), Rhizopoda (2 species) and Rotatoria (2 species). The abundance of phytoperiphyton attached in the rough surfaced ceramic was 62,370-82,470 cells/cm2 and the zooperipyton was 9,080-53,220 organisms/cm2. While in the smooth surfaced ceramic was 80,200-101,550 cells/cm2 and the zooperiphyton was 16,720-64,320 organisms/cm2. Based on the composition of periphyton, it can be concluded that the Parit Belanda River can be categorized as eutrophic.Keywords: Parit Belanda River, Periphyton, Rough surfaced ceramic and Smooth surfaced ceramics